(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract. This article discusses Dabusiya fortress and its neighboring cities on theGreat Silk Road, and considers the specific aspects of the cities